ACTIV ATED CARBON FROM INDIGENOUS INFERIOR WOODS Part- V. Granular Activated Carbon Preparation and Liquid Phase Characterization - USMAN , TANZL H.; AHMAD, TAMOOR WAHAB; MUMTAZ , MOHAMMAD; MOTAN , M. TAHIR; YOUSAFZA , A.H.K. (Biological Sciences - PJSIR, 2022)
The effect of zinc chloride in different impregnation ratios on various physical and chemical properties of granular activated carbon prepared from saw dust (0.250-0.473 mm) of ’Babul’ (Acacia arabica) has been studied. It has been found that zinc chloride acts both as an activating agent as well as a binder during this process. The suitability of gelatinous mass used for granulization with different impregnation ratios has been studied and an appropriate ratio established. The activity of the product has been evaluated in liquid phase against adsorbates of different molecular dimensions. Granular carbon suitable for adsorption of small and larger molecules (micro and meso) may be prepared by chemical impregnation method.